The Influence of Environmental Knowledge on Pro-Environmental Lifestyles of UI Vocational Students Domiciled in the Jabodetabek Area - Ekadyasa, Sartika; Krypton, Arius (Jurnal Vokasi Indonesia, 2025)
The environmental crisis demands the younger generation, especially students, to play an active role in implementing an environmentally friendly lifestyle. This study aims to determine the influence of environmental knowledge on the pro-environmental lifestyle of students in the Jabodetabek area. Using a quantitative survey method on 100 students, the data was analyzed through simple linear regression. The results showed that environmental knowledge significantly influenced pro-environmental lifestyle (p < 0.05), while family support and access to environmentally friendly facilities also played important roles. These findings support the importance of environmental education at the college level to shape sustainable behavior.